2009
DOI: 10.1111/igc.0b013e3181a8335e
|View full text |Cite
|
Sign up to set email alerts
|

Adnexal Mass Vascularity Assessed by 3-Dimensional Power Doppler: Does It Add to the Risk of Malignancy Index in Prediction of Ovarian Malignancy?

Abstract: The Risk of Malignancy Index (RMI) is used for the prediction of ovarian malignancy. It includes menopausal status, carbohydrate antigen 125 serum levels, and ultrasound criteria. Three-dimensional power Doppler (3-DPD) is a reproducible investigation for assessment of tumor vascularity, classifying vascularity to avascular, parallel, and chaotic patterns. In this study; 3-DPD was added to RMI for prediction of malignancy in 400 cases of ovarian masses. Sensitivity of RMI for prediction of malignancy was 88%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…They believe that objective quantification of the color content of the tumor scan using three-dimensional Power Doppler ultrasound does not seem to add more to gray-scale imaging than does subjective quantification by the ultrasound examiner using two-dimensional Power Doppler ultrasound [23]. Also, one could state that there is no sufficient explanation what are possible advantages of three-dimensional Power Doppler over other more simple methods such as conventional “pattern recognition” or the so called “Risk of Malignancy Index” (RMI) method which use only two-dimensional sonographic imaging [24]. In a recent study, it has been shown that in over 400 tumors examined by three-dimensional Power Doppler and RMI the sensitivity of RMI for prediction of malignancy was 88%, with a cutoff value of 202.5 at 95% confidence interval whereas the sensitivity of three-dimensional Power Doppler for prediction of malignancy was 75% while adding three-dimensional Power Doppler to RMI increased its sensitivity to 99% [24].…”
Section: Discussionmentioning
confidence: 99%
“…They believe that objective quantification of the color content of the tumor scan using three-dimensional Power Doppler ultrasound does not seem to add more to gray-scale imaging than does subjective quantification by the ultrasound examiner using two-dimensional Power Doppler ultrasound [23]. Also, one could state that there is no sufficient explanation what are possible advantages of three-dimensional Power Doppler over other more simple methods such as conventional “pattern recognition” or the so called “Risk of Malignancy Index” (RMI) method which use only two-dimensional sonographic imaging [24]. In a recent study, it has been shown that in over 400 tumors examined by three-dimensional Power Doppler and RMI the sensitivity of RMI for prediction of malignancy was 88%, with a cutoff value of 202.5 at 95% confidence interval whereas the sensitivity of three-dimensional Power Doppler for prediction of malignancy was 75% while adding three-dimensional Power Doppler to RMI increased its sensitivity to 99% [24].…”
Section: Discussionmentioning
confidence: 99%
“…Combining the risk of malignancy index with 3D power Doppler sonography in a logistic regression model resulted a 99% sensitivity rate for malignant lesion recognition; however, the authors did not specify the tool for clinical application. 21 The use of 3D power Doppler sonography turned out to be beneficial in ovarian fibromas, in which the risk of malignancy index may falsely indicate a suspected malignancy due to their solid component and frequent ascites (Meigs syndrome), as well as in cases of endometriosis, since a high serum CA-125 level may result in a false-positive risk of malignancy index value. 21 An innovative computer-aided diagnostic technology that quantifies characteristic features of backscattered ultrasound theoretically allows transvaginal sonography to discriminate benign from malignant adnexal masses.…”
Section: Other Indices Comprising a Combination Of Variablesmentioning
confidence: 99%
“…21 The use of 3D power Doppler sonography turned out to be beneficial in ovarian fibromas, in which the risk of malignancy index may falsely indicate a suspected malignancy due to their solid component and frequent ascites (Meigs syndrome), as well as in cases of endometriosis, since a high serum CA-125 level may result in a false-positive risk of malignancy index value. 21 An innovative computer-aided diagnostic technology that quantifies characteristic features of backscattered ultrasound theoretically allows transvaginal sonography to discriminate benign from malignant adnexal masses. 70 The examination starts with conventional 2-dimensional transvaginal sonography for identifying adnexal masses, followed by a standardized 3D transvaginal sonography procedure to capture 3D images for determining the volumes of interest to be analyzed by histoscanning.…”
Section: Other Indices Comprising a Combination Of Variablesmentioning
confidence: 99%
“…56 Several subsequent studies, using all of them similar criteria for malignancy suspicion, reported similar findings: 3D PD vascular tree assessment adds little to conventional ultrasound. [57][58][59][60] These studies are summarized in Table 3.…”
Section: Adnexal Tumorsmentioning
confidence: 99%